2018
DOI: 10.7196/samj.2018.v108i11.13095
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among HIV-serodiscordant couples in Durban, South Africa

Abstract: Background. South Africa (SA) has a high prevalence rate of intimate partner violence (IPV) and HIV, both of which can be exacerbated further by HIV serodiscordancy in the couple dyad. Further exploration of the discordancy sidedness in known mediating factors, such as alcohol abuse risk and post-traumatic stress (PTS), is required. Objectives. To investigate the extent of and gender differences in IPV, alcohol abuse risk and PTS symptoms among HIV-serodiscordant couples in Durban, SA, and to analyse these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…This review also reports on structural barriers such as sexual and interfamily violence suffered by WLHIV when disclosing their serostatus to partners and family members, in addition to perceived stigma and discrimination that continues to permeate social and family relations in LAC . Similar results were described in South Africa where authors reported high levels of intimate partner violence in HIV‐serodiscordant couples and by Kennedy et al., who demonstrated how interventions carried out with WLHIV, partners and families to facilitate disclosure of HIV status improve health outcomes, facilitate safe sexual behaviours and empower women to report violence. These highly effective interventions, adapted to their context, should be considered by LAC countries as part of the care provided in public health settings .…”
Section: Discussionmentioning
confidence: 59%
“…This review also reports on structural barriers such as sexual and interfamily violence suffered by WLHIV when disclosing their serostatus to partners and family members, in addition to perceived stigma and discrimination that continues to permeate social and family relations in LAC . Similar results were described in South Africa where authors reported high levels of intimate partner violence in HIV‐serodiscordant couples and by Kennedy et al., who demonstrated how interventions carried out with WLHIV, partners and families to facilitate disclosure of HIV status improve health outcomes, facilitate safe sexual behaviours and empower women to report violence. These highly effective interventions, adapted to their context, should be considered by LAC countries as part of the care provided in public health settings .…”
Section: Discussionmentioning
confidence: 59%
“…Firstly, the researchers, through their experience with working with people living with HIV, identified a gap in the services that were available to assist couples with a different HIV status, with most counselling services focussing on voluntary counselling and testing for individuals (Mashaphu & Burns, 2017). Secondly, a systematic literature review was conducted to look at psychosocial interventions that have been used with success within the African context, with a special emphasis on cultural congruency, efficacy and sustainability which can be applied in the real world for the greater benefit of the public (Mashaphu et al, 2018a(Mashaphu et al, , 2018b. Thirdly, Eban II was identified for adaptation through a transdisciplinary collaborative initiative between South Africa and the United States, which allowed the researchers an opportunity to receive training from the Eban II research team.…”
Section: Methodsmentioning
confidence: 99%
“…When partners make aware of their HIV status together in serodiscordant relationships often face major challenges including gender-based violence, lack of sexual desire, divorce and abandonment, self-blaming, the stress of possible transmission, nancial pressures, HIV-related stigma, family breakdown, desertion and isolation; all of which may have a negative in uence on their relationships (11)(12)(13)(14)(15). A study conducted on serodiscordant couples, indicated that exposure to intimacy violence partner differed signi cantly between men (28.6%) and women (89.3%) (16). Mashaphu (2018) argued that there is a high level of intimacy violence partner in HIV serodiscordant couples, therefore, intervention programs should address gender-based violence and inequity among heterosexual couples (16).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on serodiscordant couples, indicated that exposure to intimacy violence partner differed signi cantly between men (28.6%) and women (89.3%) (16). Mashaphu (2018) argued that there is a high level of intimacy violence partner in HIV serodiscordant couples, therefore, intervention programs should address gender-based violence and inequity among heterosexual couples (16). Patel (2016) suggested that counseling programs in relation to intimate partner violence may be important in preventing the risk of HIV transmission to HIVnegative wives (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation